2019
DOI: 10.1101/744763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NRP2 as an emerging angiogenic player; promoting endothelial cell adhesion and migration by regulating recycling of α5 integrin

Abstract: Angiogenesis relies on the ability of endothelial cells (ECs) to migrate over the extracellular matrix via integrin receptors to respond to an angiogenic stimulus. Of the two neuropilin (NRP) orthologs to be identified, both have been reported to be expressed on normal blood and lymphatic ECs, and to play roles in the formation of blood and lymphatic vascular networks during angiogenesis. Whilst the role of NRP1 and its interactions with integrins during angiogenesis has been widely studied, the role of NRP2 i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 72 publications
(100 reference statements)
1
8
0
Order By: Relevance
“…We have previously shown that endothelial NRP2 drives a VEGF‐independent, Rac1‐mediated mechanism of cell adhesion and migration over fibronectin (FN) matrices and regulates FA turnover by promoting basal α5‐integrin recycling 24 . Here we show that NRP2 regulates VASP‐mediated control of actin pattern development to support the protrusion of dynamic lamellipodia at the leading edge of migrating cells.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…We have previously shown that endothelial NRP2 drives a VEGF‐independent, Rac1‐mediated mechanism of cell adhesion and migration over fibronectin (FN) matrices and regulates FA turnover by promoting basal α5‐integrin recycling 24 . Here we show that NRP2 regulates VASP‐mediated control of actin pattern development to support the protrusion of dynamic lamellipodia at the leading edge of migrating cells.…”
Section: Introductionmentioning
confidence: 63%
“…We have previously used multiple specific NRP2 siRNAs in both immortalized and primary mouse‐lung microvascular ECs (mLMECs) to identify endothelial NRP2 as a key regulator of EC adhesion and migration by promoting FA turnover and Rac1 activation, independent of VEGF‐stimulation. Label‐free quantitative mass spectrometry was additionally utilized to elucidate candidate NRP2 interactions with several endocytic and recycling‐associated trafficking proteins 24 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Robinson is also partially funded by the BBSRC Institute Strategic Programme Gut Microbes and Health BB/R012490/1 and its constituent project (BBS/E/F/000PR10355). This manuscript has been released as a pre-print at BioRxiv (Alghamdi et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%